GAMBARAN TINGKAT STRES MAHASISWA KEPERAWATAN UNIVERSITAS UDAYANA DALAM PROSES PEMBELAJARAN SELAMA PANDEMI COVID-19 - Khrismadani, Putu Herma; Sawitri, Ni Komang Ari; Nurhesti, Putu Oka Yuli (Coping: Community of Publishing in Nursing; Vol 10 No 2 (2022): April 2022, 2022)
Stress is a psychological response experienced by each individual where the individual is faced with things that are felt to have exceeded the limit or are considered difficult to deal with. Students are one of the groups that are very vulnerable to stress. Moderate to severe stress levels experienced by students can hinder the learning process. This study aims to describe the stress level of Udayana University nursing students in the learning process during the Covid-19 pandemic. This research uses descriptive quantitative method with cross sectional design. One hundred and sixty-one out of 270 students were selected by stratified random sampling method. Data were collected using a research adaptation questionnaire. The results of this study indicate that most students experience moderate stress. Stress is seen from several aspects, namely physical, emotional, intellectual, and interpersonal. Based on gender, the stress level was found to be high in female students compared to male students. Based on the class, the highest stress level was found in the class of 2020. Based on the GPA, the stress level was high in the GPA with praise. Based on the status of residence, the stress level was found to be high in students with the status of living with their parents. Changes in learning methods are one of the triggering factors for psychological changes. The adaptation process is able to cause a stressful impact for students, because the readiness of students in online learning is not yet mature.